Breaking down employment barriers for PWDs: Disability inclusion in the Philippine hospitality industry - Avecilla, Johneena Ellizze V.; Cedeño, Fritzie Joy C.; Gloriani, Maria Madelaine L.; Millevo, Marie Celine T.; Sanchez, Zach Bryant; Andalecio, Avi Ben Pestañas (School of Tourism, Universitas Ciputra Surabaya, 2024)
Despite numerous local and international statutes on their acceptance in mainstream employment, persons with disabilities (PWDs) still experience various forms of discrimination. The actions that the PWDs get may result in the way how other people treat them, or the improper stereotypes that the employers perceive them to be. Hence, underemployment among PWDs is still one of the problems in the society, mainly because some are having difficulties in being employed due to their condition. Persons with Disabilities have been fighting for their rights in the workforce for a long time in the Philippines. Despite all the efforts of the government and advocacies of the private sector, employment among PWDs has been difficult and rigorous. There have been different multi-sectoral movements to lobby for change especially in the hospitality sector. Hence, focusing on the views of the key-players are the main objective of this investigation. The goal of this paper is to understand the view of government and private sectors in hiring PWDs in the hospitality establishments of the National Capital Region (NCR) of the Philippines. Phenomenology, a qualitative type of technique, was employed in the study. The researchers collected the data through semi-structured face-to-face interviews and implemented a thematic analysis to create themes based on extracted codes. The findings of this study come from the views of public and private sectors, the government’s involvement, the implementation of Republic Act 7277 or Magna Carta for PWDs, and the hiring process associated with hiring PWDs. The researchers concluded that the government and private sectors are gearing towards inclusive growth by hiring PWDs in the National Capital Region, Philippines, despite the social stigmas associated with hiring them.